p^2+9p+27=0

Simple and best practice solution for p^2+9p+27=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p^2+9p+27=0 equation:


Simplifying
p2 + 9p + 27 = 0

Reorder the terms:
27 + 9p + p2 = 0

Solving
27 + 9p + p2 = 0

Solving for variable 'p'.

Begin completing the square.

Move the constant term to the right:

Add '-27' to each side of the equation.
27 + 9p + -27 + p2 = 0 + -27

Reorder the terms:
27 + -27 + 9p + p2 = 0 + -27

Combine like terms: 27 + -27 = 0
0 + 9p + p2 = 0 + -27
9p + p2 = 0 + -27

Combine like terms: 0 + -27 = -27
9p + p2 = -27

The p term is 9p.  Take half its coefficient (4.5).
Square it (20.25) and add it to both sides.

Add '20.25' to each side of the equation.
9p + 20.25 + p2 = -27 + 20.25

Reorder the terms:
20.25 + 9p + p2 = -27 + 20.25

Combine like terms: -27 + 20.25 = -6.75
20.25 + 9p + p2 = -6.75

Factor a perfect square on the left side:
(p + 4.5)(p + 4.5) = -6.75

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| ln(x-6)+ln(x+5)=ln(x-31) | | -30-3x=12-3x | | -3x-8+4=7 | | 2/5(x)=8 | | kx-3x=w | | .20(16)+.100(b)=.30(16+b) | | 6u-v+x=9x+w | | 59x-6x=8x+17 | | -20x=-80 | | 4(3-7y)+10=-10y-86 | | x^2-17x-60= | | g(p+4)=3p^2+27p+81 | | 1/3/4=x | | 180+218+x/3= | | -3x^2-36x-109=0 | | 5(7-2x)+13=9x+48 | | 5(k-4)-3(k-6)=0 | | 16y-4=12y+8 | | .06x+.08(18000-x)=1290 | | -2w-1=0 | | 67-5=40x+17 | | x^3+8x^2+13x-2=0 | | 8x+10=13x-5 | | y+4+2y=13 | | 2x+38=9x+39 | | 17a-20b+2c+2c-3b-6a= | | 1.2(2x-4)+0.6=3x-3.6 | | -4y^2+4y-1=0 | | 54t+14.6-10.1t=12.8-3.5t-0.6 | | 19p-12q+p-7q-3p= | | -6x^2+16x-8=0 | | 7(x+5)=4(8x+40) |

Equations solver categories